Peran Etika Media dalam Mencegah Penyebaran Fitnah di Era Digital: Tantangan dan Solusi : The Role of Media Ethics in Preventing the Spread of Defamation in the Digital Era: Challenges and Solutions - Ridwan, Ridwan; Kamaluddin Tajibu (Litera Academica Publishing, 2025)
In the digital information era, media plays a vital role in disseminating news and shaping public opinion. However, it also faces significant challenges, particularly in the spread of defamation, which can harm the reputation of individuals, groups, or institutions. This study aims to analyze media ethics principles in avoiding defamation, including information verification, independence, fairness, and caution, while identifying contributing factors such as lack of journalistic professionalism, influence of vested interests, and the role of social media. Using a qualitative descriptive-analytical approach, the research explores strategic measures to prevent defamation, such as journalistic ethics training, internal supervision, strict regulations, and enhancing media literacy. This study aspires to contribute to more responsible reporting, promote media integrity, and foster a critical and informed society.